2010
DOI: 10.1108/02683941011056987
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with work‐family balance among German office workers

Abstract: Purpose -The paper seeks to examine the relationships between various work demands and resources and satisfaction with work-family balance in a sample of German office workers. Work-to-family conflict is expected to mediate several relationships between dependent and independent variables. Design/methodology/approach -A sample of 716 office workers from two service sector organizations in Germany participated in a comprehensive online survey. Hierarchical multivariate regressions were used to test the predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 84 publications
(132 reference statements)
12
70
0
7
Order By: Relevance
“…The studies mostly showed that JI was related to higher WFC (Batt & Valcour, 2003;Beham & Drobnic, 2009;Hughes, Galinsky, & Morris, 1992;Richter, Näswall, & Sverke, 2010;Ruokolainen, Mauno, & Cheng, 2014;Voydanoff, 2004Voydanoff, , 2005 and FWC (Kinnunen & Mauno, 1998;Voydanoff, 2007). Studies on the experiences of positive work-family interface reported that JI was also associated with lower work-to-family enrichment (over-time effect if baseline of enrichment was not taken into account; Cheng, Mauno, & Lee, 2014a), lower work-tofamily facilitation (only if other work characteristics were not taken into account, Voydanoff, 2005), and lower satisfaction with work-family balance (via WFC as a mediator; Beham & Drobnic, 2009). Furthermore, JI was found to be associated with poorer marital role quality (Barling & Macewen, 1992;Cheng, Mauno, & Lee, 2014b;Hughes & Galinsky, 1994;Hughes et al, 1992;Larson, Wilson, & Beley, 1994;Mauno & Kinnunen, 1999a; see Table 2) in the form of marital dissatisfaction, marital tension, and poorer marital adjustment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies mostly showed that JI was related to higher WFC (Batt & Valcour, 2003;Beham & Drobnic, 2009;Hughes, Galinsky, & Morris, 1992;Richter, Näswall, & Sverke, 2010;Ruokolainen, Mauno, & Cheng, 2014;Voydanoff, 2004Voydanoff, , 2005 and FWC (Kinnunen & Mauno, 1998;Voydanoff, 2007). Studies on the experiences of positive work-family interface reported that JI was also associated with lower work-to-family enrichment (over-time effect if baseline of enrichment was not taken into account; Cheng, Mauno, & Lee, 2014a), lower work-tofamily facilitation (only if other work characteristics were not taken into account, Voydanoff, 2005), and lower satisfaction with work-family balance (via WFC as a mediator; Beham & Drobnic, 2009). Furthermore, JI was found to be associated with poorer marital role quality (Barling & Macewen, 1992;Cheng, Mauno, & Lee, 2014b;Hughes & Galinsky, 1994;Hughes et al, 1992;Larson, Wilson, & Beley, 1994;Mauno & Kinnunen, 1999a; see Table 2) in the form of marital dissatisfaction, marital tension, and poorer marital adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, mediator analyses showed that WFC mediated the relationship between JI and family outcomes such as marital tension (Hughes et al, 1992) and employees' satisfaction with work-family balance (Beham & Drobnic, 2009), and FWC (Voydanoff, 2005). Moreover, moderator analyses revealed that some work characteristics, e.g., high job commitment/engagement, rendered employees more vulnerable to the harmful role of JI in family (parental dissatisfaction; Ruokolainen et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Behan & Drobnic, 2010;Carlson et al, 2010;Calvo-Salguero, Carrasco-Gonzalez, & Salinas Martinez, 2010;Lourel, Ford, Gamassou, Gueguen, & Hartmann 2009;Cohen, 2009;Carly et al, 2002). However there are relatively less studies in the collectivist societies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Lepine et al, 2004;Voydanoff, 2005a,b;Scherer and Steiber, 2009;Valcour, 2007;Schieman et al, 2009;Steiber, 2009;Beham and Drobnič, 2010;den Dulk et al, 2011). Podsakoff et al (2007) also found in their meta-analysis of previous research that both challenge and hindrance stressors were positively associated with strain, which may render it very difficult for individuals to invest resources in family successfully.…”
Section: Work Stress and Work-family Conflictmentioning
confidence: 90%